IMPROVING THE RESULTS OF IPS STUDY USING NUMBERED HEADS TOGETHER (NHT) MODEL IN SD - Andria, Pratiwi; M.Pd, Dra. Zuraida; M.Pd, Dra. Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study was to describe the improvement of student learning outcomes in social studies learning using the Numbered Heads Together (NHT) model in class IV SDN 18 fields laweh padang lua, regency, in 25 students. This research uses qualitative and quantitative approach. The type of research is Classroom Action Research (PTK). Student learning outcomes in cycle I on average 73.17 increased to 80.32 in cycle II. Thus, the Numbered Heads Together (NHT) model can improve student learning outcomes in social studies learning in class IV SDN 18 Ladang laweh padang lua, regency of Agam.